The Effect of Service Quality, Servicescape, Brand Image, and Trust on Customer Satisfaction - Purnamasari, Imas Ayu; Miftahuddin, Muchammad Agung; Rachmawati, Erny; Suyoto, Suyoto (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study will look at how service quality, servicescape, brand image, and trust affect customer happiness at Burger Bangor Purwokerto. This study employs quantitative methodologies, with data collected via questionnaires disseminated online. The data used is original data, with up to 135 samples. Technical data analysis with SPSS 27. The findings revealed that service quality, servicescape, brand image, and trust all influence consumer satisfaction. Service quality, service landscape, brand image, and trust all have a positive and significant impact on customer satisfaction. The findings of this study can help Burger Bangor Purwokerto better its operational strategy, particularly in terms of service quality, servicescape, brand image, and trust, in order to retain customer loyalty and increase competition in the fast food business.